ANALISIS KONTRASTIF INFLEKSI DAN DERIVASI DALAM BAHASA ARAB DAN BAHASA INDONESIA (KAJIAN MORFOLOGI DESKRIPTIF) - Solihin, Muhammad; Muhsinin, Muhsinin (Universitas Islam Negeri Mataram, 2023)
The aim of this research is to analyze the differences and similarities between Arabic and Indonesian in terms of inflectional morphology and derivations. The type of research used is a descriptive qualitative research method with a contrastive synchronic approach. Data collection methods and techniques in this research used listening methods and note-taking techniques. The results obtained from this research are that there are similarities and differences in the inflection and derivation processes in Arabic and Indonesian. The similarity is that in the inflection process both of them get changes in the verb (verb), nominal (noun) and adjective (adjective). Likewise, in the derivation process, both of them receive additions at the beginning, middle and end in order to obtain a specific meaning or goal. The difference between Arabic and Indonesian in the inflection and derivation process is that Arabic is more productive than Indonesian both in terms of inflection and derivation.